Linguistic Thoughts as The Basis of Arabic Learning Innovation - Thonthowi, Thonthowi (Universitas Islam Negeri Raden Intan Lampung, 2018)
AbstractThis study aims to discuss linguistic thoughts and Arabic learning in Indonesia, along with both innovation opportunities and their actualization in the development of Arabic learning. This study is literary with an intertextual approach to the literature associated with two fields. The meaning of the text is done by content analysis. This study concludes that the innovation of linguistic thoughts and Arabic learning can be done on three levels, namely Arabic linguistic study and development, contextualization of Arabic research methodology, and standardization of ICT-based Arabic language learning and research. Various problems surrounding learning Arabic language can be solved through research and study of Arabic linguistics in depth, comprehensive and cross-disciplinary of science. Opportunities to innovate linguistic thoughts and language learning are wide open. Various scientific forums and journals as well as research in Arabic-based learning development of linguistic thought can lead to tajdîd (reform, innovation) and ijtihâdat lughawiyyah (linguistics innovation). The future of linguistic studies and Arabic learning in Indonesia is believed to be very bright and enlightening if reinforced by the development of linguistic research meth- ods and Arabic learning.Keywords:Innovation, linguistic thought, Arabic learning, linguistic research, scientific and academic forums